The effect of framework flexibility on diffusion of small molecules in the metal-organic framework IRMOF-1 - Ford, Denise C.; Dubbeldam, David; Snurr, Randall Q. (Diffusion Fundamentals, 2009)
Many efforts have been made to model adsorption and diffusion processes in metalorganic frameworks (MOFs) in the past several years. In most of these studies, the framework has been kept rigid. In this study, we examine the effect of using a flexible framework model on the self-diffusion coefficients and activation energies calculated for several short n-alkanes and benzene in IRMOF-1 from molecular dynamics simulations. We find only minor differences between flexible and rigid framework results. The selfdiffusion coefficients calculated in the flexible framework are 20-50% larger than the ones calculated in the rigid framework, and the activation energies differ by only 10-20%.